Evaluating the Impact of Team-Assisted Individualization and Team Games Tournament Approaches on Student Engagement in Science Learning - Sintha Wahjusaputri; Ernawati Ernawati; Abu Yazid; Muhammad Anwari; Rona Norhana Dewi (STAI Hubbulwathan Duri, 2024)
This study assesses the efficacy of the Teams Assisted Individualization (TAI) and Teams Games Tournament (TGT) learning models in enhancing academic performance and engagement among Mathematics students. Utilizing a classroom action research approach, the study was conducted over two cycles, each comprising four stages: observation, initial data collection, implementation planning of TAI and TGT, and report preparation. The participants included 72 students from classes VII A and VII B. The research revealed significant improvements in student performance. In class VII A, utilizing TAI, the percentage of students meeting the minimum competency level (KKM) increased from 45% in the pre-action phase to 85% by the end of Cycle II. Similarly, in class VII B, under the TGT model, the percentage of students achieving the KKM rose from 55% to 92%, with completion rates of assigned tasks also showing notable improvements. The findings suggest that both TAI and TGT models are effective in promoting higher academic achievement and greater student engagement in Mathematics. The substantial increase in students meeting the KKM and completing tasks indicates that these collaborative learning strategies significantly enhance learning outcomes. Implementing the TAI and TGT collaborative learning models has proven beneficial in boosting engagement, motivation, and academic performance among seventh-grade students at SMPN 243 Jakarta in their Mathematics coursework.